Probucol: revisiting as a multifaceted therapeutic agent in atherosclerosis - Li, Sha; Liu, Hui-Hui; Xu, Rui-Xia; Li, Jian-Jun (Frontiers in Pharmacology, 2026)
Atherosclerotic cardiovascular disease (ASCVD) is known to be driven by chronic inflammation and pro-atherogenic dyslipidemia and remains as one of the leading causes of mortality globally. Despite the success of current lipid-lowering therapies, a significant residual inflammatory risk persists, highlighting the need for treatments with broader mechanisms. Probucol is a lipid-modulating agent with uniquely potent antioxidant and anti-inflammatory properties that is re-emerging as a compelling multifunctional drug against atherosclerosis. This review critically examines the available evidence on probucol’s impacts on ASCVD, with special focus on its integrated effects on the cholesterol–inflammation pathway. We examine the pleiotropic mechanisms of this drug, including the inhibition of low-density-lipoprotein oxidation and reverse cholesterol transport potentiation, as well as appraise the clinical data demonstrating its ability to regress atherosclerotic plaques and reduce cardiovascular events. While acknowledging the controversies that have limited the use of probucol, such as its high-density-lipoprotein cholesterol-lowering effect and risk of QT prolongation, we provide an updated and balanced perspective on its risk–benefit profile. By compiling existing knowledge from mechanistic and clinical studies, this review argues for a reappraisal of probucol’s role and outlines future directions needed to establish its place in the modern management of atherosclerosis.